Low cost satellite constellations for nearly continuous global coverage - Lake A. Singh (Nature Portfolio, 2020)
Telecommunication, navigation and remote sensing services are highly dependent on how well satellites provide global coverage. Here the authors show a pair of four-satellite low-cost longer-life constellations that provide nearly continuous global coverage to support Earth observation.